Avaliação eletromiográfica dos músculos envolvidos na alimentação de recém nascidos prematuros - Camila Dantas Martins (2013)
Introduction: some neonates, due to the immaturity of the oral sensory-motor system, may not be orally fed, being necessary the use of other feeding methods such as for instance the use of cup. Objectives: to measure and compare the electrical activity of masseter, temporal, and suprahyoid muscles in premature newborn infants during breastfeeding and cup-feeding. Methods: this was a cross-sectional study was carried out by means of the electromyographic assessment of preterm infants, clinically stable, fed via oral route, by full breastfeeding and supplementation of diet, through cup with expressed breastmilk, until 15 days after hospital discharge. Children with neurological disorders, genetic syndromes, oral-motor and/ or congenital malformations were excluded. The different methods of feeding and the variables gestational age at birth, corrected gestational age, birth weight, Apgar scores at 1 and 5 minutes, were analyzed and compared by means of appropriate statistical analysis. Results: the sample was composed of 36 preterm newborns, 53% of whom were male, with mean gestational age of 32 weeks and birth weight of 1.700g . There was no statistically significant difference between breastfeeding and cup-fedding. However, the analysis of the temporal and masseter muscles showed higher activity of supra hyoid musculature during cup-feeding (p= 0,001). The correlation among the activity of masseter, temporal, and supra-hyoid muscles to the different variables, showed a significant correlation for the activity of the masseter muscle during breastfeeding and the value of the Apgar score at 1 minute (p= 0,03). Conclusion: two methods of feeding were similar. The results suggest that balance between the activities of temporal and masseter muscles during breastfeeding and cup-feeding, although, the suprahyoid muscles are more active during cup-feeding.